1984
DOI: 10.1302/0301-620x.66b3.6725342
|View full text |Cite
|
Sign up to set email alerts
|

A six-year follow-up of infected total hip replacements managed by Girdlestone's arthroplasty

Abstract: Thirty-three Girdlestone's arthroplasties used to salvage infected total hip replacements were followed for a mean of 6.2 years to assess the efficacy of this procedure. Subjective and objective assessment was obtained at the time of review. Gram-negative organisms, retained cement, bony sequestra and secondary healing were common features of the five patients (15%) whose wounds discharged for more than four weeks after operation. Girdlestone's arthroplasty provided satisfactory pain relief in 91% of patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
0
12

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 0 publications
9
53
0
12
Order By: Relevance
“…Deep infection complicates between 1% and 2% of total hip replacements [2,4,6]. Clegg advocated complete removal of all the cement remnants in order to achieve eradication of infection [7], but we agree with the views of others that small amounts of retained cement do not seem to influence wound healing after resection arthroplasty [1,4,13].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Deep infection complicates between 1% and 2% of total hip replacements [2,4,6]. Clegg advocated complete removal of all the cement remnants in order to achieve eradication of infection [7], but we agree with the views of others that small amounts of retained cement do not seem to influence wound healing after resection arthroplasty [1,4,13].…”
Section: Discussionmentioning
confidence: 52%
“…Patients with severe loss of bone stock, risk of recurrent infection or poor general condition [2,4,9,11] may not be suited for further major interventions, especially one-or two-stage reimplantation after failed primary total hip replacement. In such cases, Girdlestone resection arthroplasty is considered to be an acceptable option.…”
Section: Introductionmentioning
confidence: 99%
“…Reimplantation of a prosthesis into a long standing pseudarthrosis can be technically difficult and the patients should be carefully selected [3]. The indications are poor function and pain.…”
Section: Discussionmentioning
confidence: 99%
“…The pseudarthrosis remains a reasonable salvage operation for special problems [3], but reimplantation Fig. 3a-c.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, in the presence of osteomyelitis of the femur and dislocation, excision arthroplasty would have been the first choice in adults. Although the Girdle stone procedure [6,7] may reduce pain, the functional outcome is often poor. Studies of the conversion of a Girdle stone pseud arthrosis to an arthroplasty have shown improvements in the Harris hip score 8 personal satisfaction and activities of daily living, but only in the absence of infection [8][9][10].…”
Section: Discussionmentioning
confidence: 99%